2006
DOI: 10.3727/152599507783948675
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Approach to Analyzing Local Expenditures and Visitor Profiles of two Wildlife Festivals

Abstract: Wildlife festivals are growing in popularity and warrant additional studies of festival visitors. However, comparisons of visitor demographics, motivations, activities, and local expenditure patterns between festivals are difficult because different methods of measurement are used. By using a comparative approach, this study evaluates, with the same methods, the visitor characteristics of two similar wildlife festivals in Western Canada. While providing site-specific context, this study notes variations in tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…In general, birding is the fastest-growing outdoor recreational activity in U.S. and the most promising branch of ecotourism in terms of economic impacts, with a high potential to contribute to local communities (Şekercioğlu 2003 ). Although little quantified, specific non-consumptive interest in geese is increasing the U.S. and Canada and 2–3 day goose festivals geared specifically for greater snow or brent geese attract thousands of visitors, bringing substantial local economic benefit (Hvenegaard and Manaloor 2006 ; SGSBC 2009 ; Hvenegaard 2011 ). The annual revenue from birdwatching and eco-tourism in the four main spring staging areas of greater snow geese in Québec was estimated at c. US$14 million (Bélanger and Lefebvre 2006 ).…”
Section: Ecosystem Services and Disservices By Wild Geese Populationsmentioning
confidence: 99%
“…In general, birding is the fastest-growing outdoor recreational activity in U.S. and the most promising branch of ecotourism in terms of economic impacts, with a high potential to contribute to local communities (Şekercioğlu 2003 ). Although little quantified, specific non-consumptive interest in geese is increasing the U.S. and Canada and 2–3 day goose festivals geared specifically for greater snow or brent geese attract thousands of visitors, bringing substantial local economic benefit (Hvenegaard and Manaloor 2006 ; SGSBC 2009 ; Hvenegaard 2011 ). The annual revenue from birdwatching and eco-tourism in the four main spring staging areas of greater snow geese in Québec was estimated at c. US$14 million (Bélanger and Lefebvre 2006 ).…”
Section: Ecosystem Services and Disservices By Wild Geese Populationsmentioning
confidence: 99%
“…According to Duffus and Dearden (1990), among the new participants to wildlife festivals (i.e., soft ecotourism), there will be more generalists than specialists. This has been shown in several wildlife festivals (Chambliss, Slotkin, & Vamosi, 2009;Fermata, Inc., 2001;Hvenegaard & Manaloor, 2007). Second, research has demonstrated considerable economic impact on local communities (Chambliss et al, 2005;Fermata, Inc., 2001;Kim, Scott, Thigpen, & Kim, 1998) and economic value of wildlife festivals (eubanks & Stoll, 1999;Fermata, Inc., 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Thus, ecotourism is characterized by nature appreciation and learning in natural settings, with management following sustainability practices for economic, sociocultural, and economic systems (ross & Wall, 1999;Weaver & lawton, 2007). Typical ecotourism activities include bird watching, whale watching, and nature study (Hvenegaard & Manaloor, 2007;Weaver, 2001). Wildlife festivals are considered to be a subset of ecotourism (Slotkin, 2003), given their similar activities and similar goals (lawton 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations